A Research for Influence of the Gear Pressure Angle on Mean Flash Temperature on Tooth Surfase - Zhang Youchen (Jixie chuandong)
This paper discussed the influence of gcar prcssure anglc on mcan flash temperature of tooth surface based on the integral tegral temperature mcthod.